A novel hydrolase PyzH catalyses the cleavage of C=N double bond for pymetrozine degradation in Pseudomonas sp. BYT‐1. (10th May 2021) - Zhang, Mingliang; Ren, Yijun; Du, Shilong; Zhou, Yidong; Jiang, Wankui; Ke, Zhijian; Jiang, Mingli; Qiu, Jiguo; He, Jian; Hong, Qing
Summary: Pymetrozine is a synthetic pesticide that can be utilized as the sole carbon source by Pseudomonas sp. strain BYT‐1. However, the genes involved in the degradation of pymetrozine remain unknown. We used transposon mutagenesis to create a mutant that unable to hydrolyze pymetrozine. The transposon interrupted the gene pyzH, which was cloned by self‐formed adaptor PCR. PyzH hydrolyzed the C=N double bond of pymetrozine to produce 4‐amino‐6‐methyl‐4, 5‐dihydro‐2 H ‐[1, 2, 4]triazin‐3‐one (AMDT) and nicotinaldehyde; the latter inhibits PyzH activity. PyzH can completely hydrolyze pymetrozine in the presence of dehydrogenase ORF6, which can convert nicotinaldehyde into nicotinic acid and relieve the inhibition. H2 18 O‐labeling experiments showed that the oxygen atom of nicotinaldehyde came from water instead of oxygen. PyzH homologous genes were also found in other soil isolates able to degrade pymetrozine.